Make lectures match how we learn: The nonlinear teaching approach to economics - Peng Zhou (Cardiff University, Cardiff Business School, 2024)
This paper proposes a nonlinear teaching approach, based on learning theories in cognitive psychology, with a special focus on large-cohort economics modules. The fundamental rationale is to match the features of teaching with the nature of learning. This approach was implemented in an undergraduate economics module, which received qualitative feedback and quantitative evaluation. Formal econometric models with both binary and continuous treatment effects were developed and estimated to quantify the effects of the proposed approach. Evidence shows that the nonlinear teaching approach significantly improves the effectiveness and efficiency of the learning-teaching process but does not promote student attendance
Keywords: A22; 330; nonlinear teaching approach; higher education; experimental action research; treatment effects